2016
DOI: 10.1186/s40337-016-0122-2
|View full text |Cite
|
Sign up to set email alerts
|

Typical patterns of disordered eating among Swedish adolescents: associations with emotion dysregulation, depression, and self-esteem

Abstract: BackgroundUsing the person-oriented approach, we determined the relationships between four indicators (restraint and eating, shape, and weight concerns) of disordered eating (DE), as measured by the self-reported Eating Disorders Examination Questionnaire (EDE-Q), to identify typical DE patterns. We then related these patterns to clinical EDE-Q cut-off scores and emotion dysregulation, depression, self-esteem, and two categories of DE behaviors (≥2 or ≤1 “yes” responses on the SCOFF questionnaire).MethodTypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
4
13
0
Order By: Relevance
“…The more pronounced DE clusters (Multiple eating problems including/without purging) were consistently associated with higher levels of psychological difficulties as well as lower levels of body esteem. The results resemble the associations between DE clusters and more severe levels of psychological problems described in the Hansson et al study [ 3 ]. The associations between DE and psychological symptoms such as depression have also been described by Herpertz-Dahlmann et al [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The more pronounced DE clusters (Multiple eating problems including/without purging) were consistently associated with higher levels of psychological difficulties as well as lower levels of body esteem. The results resemble the associations between DE clusters and more severe levels of psychological problems described in the Hansson et al study [ 3 ]. The associations between DE and psychological symptoms such as depression have also been described by Herpertz-Dahlmann et al [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
“…Although it is difficult to generalize from these results with clinical samples of adult female patients to a community sample of teenage girls, it is interesting to note that the largest cluster in Clinton et al’s [ 18 ] study showed a pattern of “generalized eating disorder”, which combined both anorexic and bulimic symptoms. This suggests the hypothesis that we may find a cluster of generally disordered eating also among young adolescents – which is also consistent with the results from Hansson et al’s [ 3 ] study. On the other hand, the three-cluster solution chosen by Clinton et al [ 18 ] may be questioned, as they do not report any data on the heterogeneity of the clusters that were arrived at.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, males had a more positive self-esteem and body image, and a lower risk of eating disorders than females, as suggested by most of the literature, because women tend to have stronger societal influences and pressures (DiPasquale & Petrie, 2013;Escobar-Molina et al, 2015;Gaines & Burnett, 2014;Hansson,Daukantaitė, &Johnsson, 2016;Kong & Harris, 2015;Stewart et al, 2014;Yilmaz,Esenturk, Ulas, &İlhan, 2017). On the other hand, there was no relationship between self-esteem, body image, and eating disorder risk.…”
Section: Discussionmentioning
confidence: 91%
“…The social construction theory (SCT) posits that social expectations, influences, beliefs, and social norms will affect individuals (Biever, De Las Fuentes, Cashion, & Franklin, 1998). Females tend to have a higher risk of eating disorder, a more negative body image, and a lower self-esteem when compared to males because they might feel more observed, assessed, and monitored due to cultural influences and pressures of society (Budzisz&Nawrocka, 2016;DiPasquale & Petrie, 2013;Escobar-Molina et al, 2015;Gaines & Burnett, 2014;Hansson et al, 2016;Kong & Harris, 2015;Stewart et al, 2014;Yilmaz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%